CAD/CAE of Jaipur foot for standardized and contemporary manufacturing. (17th February 2020) - Mali, Harlal Singh; Jain, Anil; Abrams, Lisa; Sorby, Sheryl A.; Haut Donahue, Tammy L.
Abstract: Objective: Despite immense popularity of Jaipur foot as low cost prosthetic, not much work has been reported on its design for manufacturing standardization. Without manufacturing standardization, it cannot be mass produced using contemporary manufacturing technologies. The objective of this work is to carry out its computer aided design (CAD) followed by computer aided engineering (CAE) based on the material properties obtained from the previous work [1 ] of the authors. This may lead to the possible use of modern manufacturing processes for the Jaipur foot design. Design: After modelling using CAD tool including its organic surfaces, the designed foot was analysed using a CAE tool for balanced standing load conditions to determine maximum stresses and deformation in its various parts. The bending analysis was done to check the dorsiflexion movement so that the strained sections could be identified for more reliable and durable prosthetic foot. For the static load analysis, base of the foot was constrained and 300–500 N load was applied through the bolt whereas for bending, the part near the bolt was fixed and pressure was applied at junction of front foot and toes. Results: The results show that the maximum stress and deformation occur at the bolt, while the skin undergoes maximum strain. CAE analysis also proves the robustness of the Jaipur foot design and a well manufactured Jaipur foot as per standardized design should be able to withstand the real life conditions without failure. The CAD model is also used for FDM based printing for a nonfunctional prototype of Jaipur foot. Implications for rehabilitation: The results of this study will serve as an important guideline for further research regarding equivalent material replacement, material optimization and obtaining an optimized design after studying the foot for dynamic analysis.